PENGOLAHAN KOPI DAN ANALISIS NILAI TAMBAH KOPI ROBUSTA DI KECAMATAN TUTUR KABUPATEN PASURUAN - Ramawati, Rhiska; Soedarto, Teguh; nurhadi, eko (Berkala Ilmiah AGRIDEVINA, 2019)
Tutur District is the main producer of robusta coffee commodity with the highest production in Pasuruan Regency. Coffee is a plantation commodity that can be further processed to increase value added. This study aims to determine the processing of coffee and analyze the value added of robusta coffee. This research was conducted in Tutur District, Pasuruan Regency. The analysis used is descriptive qualitative analysis and quantitative analysis through value added calculations using the Hayami methods. The results showed that coffee processing by coffee farmers in Tutur District began at levels a) cleaning b) cleaning and grading c) cleaning, grading into ose coffee d) cleaning, grading, and ose coffee into coffee powder. The average value added done by coffee farmers at the cleaning level is Rp. 311/Kg with a value added ratio of 5.1%, the average value added cleaning and grading Rp. 1.033/Kg with a value added ratio of 15.05%, the average value added of coffee ose Rp. 4,016/Kg with a value added ratio of 40.78% and an average value added of coffee powder of Rp. 18,725/Kg with a value added ratio of 52.50%. Thus, the greatest value added is found in the processing of coffee powder. This is because the more downstream a production, the higher the profits that can be. DOI : https://doi.org/10.33005/adv.v8i2.1859